Electroacupuncture Alleviates Pain-Related Emotion by Upregulating the Expression of NPS and Its Receptor NPSR in the Anterior Cingulate Cortex and Hypothalamus. (10th February 2020) - Xu, Zitong; Fang, JunFan; Xiang, Xuaner; Sun, HaiJu; Wang, SiSi; Fang, Jianqiao; Du, Junying
Abstract : Objective . Electroacupuncture (EA) is reported effective in alleviating pain-related emotion; however, the underlying mechanism of its effects still needs to be elucidated. The NPS-NPSR system has been validated for the involvement in the modulation of analgesia and emotional behavior. Here, we aimed to investigate the role of the NPS-NPSR system in the anterior cingulate cortex (ACC), hypothalamus, and central amygdala (CeA) in the use of EA to relieve affective pain modeled by complete Freund's adjuvant- (CFA-) evoked conditioned place aversion (C-CPA). Materials and Methods . CFA injection combined with a CPA paradigm was introduced to establish the C-CPA model, and the elevated O-maze (EOM) was used to test the behavioral changes after model establishment. We further explored the expression of NPS and NPSR at the protein and gene levels in the brain regions of interest by immunofluorescence staining and quantitative real-time PCR. Results . We observed that EA stimulation delivered to the bilateral Zusanli (ST36) and Kunlun (BL60) acupoints remarkably inhibited sensory pain, pain-evoked place aversion, and anxiety-like behavior. The current study showed that EA significantly enhanced the protein expression of this peptide system in the ACC and hypothalamus, while the elevated expression of NPSR protein alone was just confined to the affected side in the CeA. Moreover, EA remarkably upregulated the mRNA expression of NPS in CeA, ACC, and hypothalamus and NPSR mRNA in the hypothalamus and CeA. Conclusions . These data suggest the effectiveness of EA in alleviating affective pain, and these benefits may at least partially be attributable to the upregulation of the NPS-NPSR system in the ACC and hypothalamus.